Formulation of Sunscreen of Agarwood Leaf Ethanol Extract (Aquilaria malaccensis Lam.)Excessive exposure to sunlight can adversely affect the skin and cause various kinds of skin problems. Agarwood leaf extract (Aquilaria malaccensis Lam) contains flavon - Sari, Delia Komala; Sipriyadi, Sipriyadi; Rahmawati, Suci; Khairani, Ade (Jurnal Ilmu Kesehatan, 2024)
Excessive exposure to sunlight can adversely affect the skin and cause various kinds of skin problems. Agarwood leaf extract (Aquilaria malaccensis Lam) contains flavonoid compounds that can protect the skin from the harmful effects of UV rays. This study aims to formulate a cream from the ethanol extract of agarwood leaves (Aquilaria malaccensis Lam) which can be used as a sunscreen cream. In this study, a cream formula was prepared from ethanol extract of agarwood leaves with 3 variations of different concentrations of the extract, namely F1 2% extract of agarwood leaves, F2 4% extract of agarwood leaves and F3 8% extract of agarwood leaves. Homogeneity tests, pH tests, spreadability tests, adhesion tests, and SPF tests. The results showed that F2 with an extract concentration of 4% was the best formula with a pH of 7.11; spreadability of 6.0 cm; adhesive power of 4.9 seconds and SPF value of 39.22 which is the maximum category as a sunscreen.